(untitled) (Revista Contexto & Saúde, 2025)
Objective: To describe the epidemiological profile and distribution of hansen’s disease cases in the state of Amazonas between 2018 and 2022. Method: This is a descriptive study based on secondary data with a quantitative approach, conducted in the 62 municipalities of the state of Amazonas. Data were obtained from reported cases in the Notifiable Diseases Information System (SINAN) during the period from 2018 to 2022. Results: Sociodemographic data reveal a higher number of cases among adult males and individuals of mixed race (pardo). Hansen’s disease also more frequently affects individuals with low educational attainment. Regarding clinical characteristics, 73.9% of cases were classified as multibacillary, with the dimorphic form being predominant and physical disability commonly classified as "grade zero." There was a statistically significant association between the operational classification and the number of lesions, clinical form, and therapeutic regimen. The Southern Mesoregion recorded the highest rates of new cases, with a significant shift in this pattern only in 2022. A reduction in hansen’s disease rates was observed across all mesoregions in 2020 and 2021, reflecting the impact of the COVID-19 pandemic. Conclusion: Hansen’s disease remains a prevalent disease among vulnerable populations in the state of Amazonas, with high incidence rates in all mesoregions. Active surveillance of hansen’s disease in Amazonas is essential, focusing on early detection and reduction of transmission sources. Continuous permanent education initiatives are necessary to train healthcare professionals in the proper identification and management of hansen’s disease cases.